Identification and Bioinformatic Analysis of Circular RNA Expression in Peripheral Blood Mononuclear Cells from Patients with Chronic Obstructive Pulmonary Disease - Duan R; Niu H; Yu T; Cui H; Yang T; Hao K; Wang C (International Journal of COPD, 2020)
Ruirui Duan,1– 4 Hongtao Niu,2– 4 Tao Yu,2– 5 Han Cui,2– 4,6 Ting Yang,1– 5 Ke Hao,7 Chen Wang1– 4,6 1Peking University China-Japan Friendship School of Clinical Medicine, Beijing, People’s Republic of China; 2Department of Pulmonary and Critical Care Medicine, China-Japan Friendship Hospital, Beijing, People’s Republic of China; 3National Clinical Research Center for Respiratory Diseases, Beijing, People’s Republic of China; 4Institute of Respiratory Medicine, Chinese Academy of Medical Sciences, Beijing, People’s Republic of China; 5Institute of Clinical Medical Sciences, China-Japan Friendship Hospital, Beijing, People’s Republic of China; 6Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, People’s Republic of China; 7Department of Genetics and Genomic Sciences, Icahn School of Medicine at Mount Sinai, New York, NY, USACorrespondence: Chen WangPeking University China-Japan Friendship School of Clinical Medicine, No. 2, East Yinghua Road, Chaoyang District, Beijing 100029, People’s Republic of ChinaTel/ Fax +86-01-8420 6276Email cyh-birm@263.netPurpose: Circular RNAs (circRNAs) regulate other RNA transcripts by competing for shared microRNAs, which play roles in the pathogenesis of many diseases, including chronic obstructive pulmonary disease (COPD). However, the role of circRNAs in COPD remains unknown. This study aimed to investigate the expression profile and the role of circRNAs in COPD.Patients and Methods: Twenty-one COPD patients and twenty-one normal controls were recruited. Total RNAs were collected from peripheral blood mononuclear cells (PBMCs) of each participant. CircRNAs and protein-coding mRNAs were profiled by microarray and systematically compared between patients with COPD and control subjects. The top differentially expressed circRNAs and mRNAs were validated by quantitative real-time PCR (RT-qPCR). Functional analysis identified pathways relevant to the pathogenesis of COPD. Next, the circRNA target pathway network, the circRNA-miRNA-mRNA network (ceRNA network) and functional ceRNA regulatory modules were constructed.Results: In total, 2132 circRNAs and 2734 protein-coding mRNAs were differentially expressed (|fold change| > 1.5 and P-value < 0.05) in COPD patients. Six out of nine selected RNAs were confirmed by RT-qPCR validation. Our functional analysis suggested that immune imbalances and inflammatory responses play roles in the pathogenesis of COPD. The ceRNA network highlighted the differentially expressed circRNAs and their related miRNAs and mRNAs in COPD. In the circRNA target pathway network and functional ceRNA regulatory modules, hsa_circRNA_0008672 appeared in the top three KEGG pathways (NOD-like receptor signaling pathway, natural killer cell mediated cytotoxicity and Th17 cell differentiation) and may act as the miRNA sponge regulating the hsa_circRNA_0008672/miR-1265/MAPK1 axis.Conclusion: Our findings demonstrate critical roles of the circRNAs in COPD molecular etiology. The data support a plausible mechanism that circRNAs may be involved in the development of COPD by affecting the immune balance. Moreover, the hsa_circRNA_0008672/miR-1265/MAPK1 axis may contribute to the pathogenesis of COPD, warranting further investigation.Keywords: circular RNA, competing endogenous RNAs, chronic obstructive pulmonary disease, expression profile, co-expression network